2014
DOI: 10.1515/zpch-2014-0604
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic Surface Ligands for Colloidal Nanomaterials

Abstract: Since the discovery of metal chalcogenide complexes (MCCs) as capping ligands for colloidal nanocrystals (NCs) in 2009, the chemistry of inorganic ligands for NCs has provided a new paradigm for surface design of nanomaterials. Various inorganic anions including MCCs, metal-free chalcogenides, oxoanions/oxometallates, and halides/pseudohalides/halometallates have been employed to replace the original long-chain organic ligands on NCs. This ligand exchange can also be achieved through a two-step route using lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 61 publications
0
56
0
Order By: Relevance
“…103 In a generic method that allows the preparation of a large variety of MCCs, bulk metal chalcogenide is dissolved in hydrazine with excess chalcogenide. 103 In a generic method that allows the preparation of a large variety of MCCs, bulk metal chalcogenide is dissolved in hydrazine with excess chalcogenide.…”
Section: Ligand Orbital Mixingmentioning
confidence: 99%
See 1 more Smart Citation
“…103 In a generic method that allows the preparation of a large variety of MCCs, bulk metal chalcogenide is dissolved in hydrazine with excess chalcogenide. 103 In a generic method that allows the preparation of a large variety of MCCs, bulk metal chalcogenide is dissolved in hydrazine with excess chalcogenide.…”
Section: Ligand Orbital Mixingmentioning
confidence: 99%
“…toluene) are mixed with an immiscible polar solvent containing the ions (i.e. 103 Many NC based devices contain rectifying P-N junction which rely on stable electron-rich (n-type) NCs in addition to better investigated hole-rich (p-type) NC. 108 The ligand exchange is easily monitored as the (coloured) S 2À passivated NCs phase transfer into the polar solvent.…”
Section: Ligand Orbital Mixingmentioning
confidence: 99%
“…The ligand exchange between the existing ligand and a new one is generally based on a two-step stripping route in which the existing ligand is replaced by the new once, typically displaying higher affinity and stronger binding to the targeted surface. Ligand exchange [6,195,211,222,240,251,255,[275][276][277][278][279][280][281][282][283][284] is required to replace insulating organic surfactants and allow charge transport in nanocrystal solids as well as to prepare water-soluble nanocrystals that target specific cellular sites.…”
Section: Nanocrystal-ligand Interactions and Ligands Exchange Dynamicsmentioning
confidence: 99%
“…In this regard, a novel and fascinating approach for the post-functionalisation of nanocrystals, among which also metal sulphide colloids, is based on the use of inorganic ligands [279]. In particular, various inorganic anions including metal-free chalcogenides, oxoanions/oxometallates, and halides/ pseudohalides/halometallates have been employed to replace the original long-chain organic ligands on NCs.…”
Section: Applications-oriented Functionalisation Of Transition Metal mentioning
confidence: 99%
“…10 His group has over the years demonstrated that, with these modifications, charge mobility in nanoparticle superlattices can be greatly enhanced. 10 His group has over the years demonstrated that, with these modifications, charge mobility in nanoparticle superlattices can be greatly enhanced.…”
mentioning
confidence: 99%